EFEKTIVITAS REBUSAN KAYU MANIS DAN DAUN KERSEN TERHADAP PENURUNAN KADAR GULA DARAH - Awaluddin, Awaluddin; Nurfariza, Vera (Ensiklopedia of Journal, 2024)
Abstract :  Diabetes mellitus (DM) is still a major global health problem. This disease, commonly called sugar disease or diabetes, causes the sufferer's body to be unable to regulate blood glucose levels. One non-pharmacological therapy that can reduce blood sugar levels is cinnamon. Apart from cinnamon, cherry leaves can also lower blood sugar. The purpose of this study is to determine the effectiveness of cinnamon decoction and cherry leaves on reducing blood sugar levels in patients with type II diabetes mellitus. This quasi-experimental design is of the "pre-post-test group" type. This study used a two-group pretest-posttest design. This research was conducted on 30 April-06 May 2024. The population determined as the subjects of the study were 1227 type II diabetes mellitus patients in the Simpang Tiga Health Center Working Area. Sample of 30 people with 15 cinnamon decoction intervention groups and 15 cherry leaf decoction intervention groups. The sampling technique uses purposive sampling. Data collection tools using observation sheets. The results of the study in both samples were the same, namely 0.002 (<0.05) using an analytical test from the Wilcoxon P-Value test, so it means that there is an effect of cinnamon decoction and cherry leaves in patients with type II diabetes mellitus It is recommended that future researchers compare the effectiveness of cherry leaf decoction with other herbs, for example bay leaf decoction, to reduce blood sugar levels in patients suffering from type II diabetes mellitus. And this research can be a reference source for future researchers.Keywords : Diabetes Mellitus, Blood Sugar Levels, Cinnamon, Kersen Leaves